PENGARUH VARIASI ORIENTASI dan FRAKSI VOLUME SERAT ECENG GONDOK TERHADAP KEKUATAN UJI IMPACT KOMPOSIT SERAT ECENG GONDOK - Rosidi, Izza; Mochammad Basjir; Artono Raharjo (Universitas Islam Malang, 2023)
Composite is a group of materials made from 2 or more materials and strengthened by certain treatments. To strengthen the composite, it can be done through Alkalization treatment, meaning that the fiber is soaked in a NaOH solution for a specified time to clean the surface of the fiber so that it will increase the cellulose content by reducing the lignin and hemicellulose content. Apart from alkalization, increasing the strength of the composite can be done by treating the layout of the fiber orientation and volume fraction. The research results show that the average impact price for water hyacinth fiber composites is water hyacinth fiber composite with a volume fraction of 30; 70 and 50 : 50, namely for volume fraction 30 : 70 is continuous vertical orientation: 2, 84 joules/mm, continuous horizontal orientation: 1.44 joules/mm, random orientation: 1, 88 joules/mm then for volume fraction 50: 50 is continuous vertical orientation: 3.69 joules/mm, continuous horizontal orientation: 2.26 joules/mm, random orientation: 3.1 joules/mm. From the data that has been obtained, it shows that the most optimal impact value is in the fiber orientation. continuous vertical with a volume fraction of 50 : 50, namely 3.69 joules/mm. In this study the volume fraction was 50; 50 has the highest impact price, fiber volume greatly influences the results of the impact test